Keabsahan Jual Beli Tanah Di Wilayah Kota Depok Studi Kasus Putusan Pengadilan Negeri No. 87/Pdt.G/2018/Pn.Dpk - Imron, Ahmad; Nugroho, Meysita Arrum (Neolectura, 2024)
**The Sale and Purchase of Land According to Customary Law** refers to the transfer of rights, characterized by being *cash*, *real*, and *clear*. However, in practice, there are still instances where land sales do not fulfill the requirement of *clarity*, as in the case of District Court Decision No. 87/Pdt.G/2018/PN.Dpk. In this case, the land sale conducted between Agus Ariyanto and Sunaryo was not formalized through a deed before a Land Deed Official (PPAT), but was only evidenced by a receipt and a statement of sale and purchase. The issues raised are whether the land sale based only on a receipt constitutes a valid legal act, and whether the legal considerations and decision of the judge in case No. 87/Pdt.G/2018/PN.Dpk regarding the land sale, supported only by a receipt, align with Government Regulation No. 24 of 1997 on Land Registration. This research is a type of normative legal research and descriptive in nature. The data used are secondary data supported by primary data and analyzed qualitatively. The method of conclusion in this study employs deductive logic. Based on the results of the research, the sale and purchase of land between Agus Ariyanto (Buyer) and Sunaryo (Seller) can be considered valid under the provisions of the Civil Code (KUHPerdata) and meets the material requirements. However, the legal considerations and the judge's decision do not comply with the provisions of Government Regulation No. 37 of 1998 concerning the Regulations on the Position of Land Deed Officials.